Understanding "Wage Theft": Evasion and Avoidance Responses to Minimum Wage Increases - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2019)
A holistic assessment of the labor market effects of minimum wage regulation requires understanding employer compliance. The economics literature has paid little attention to this issue. We investigate how minimum wage increases and the strength of enforcement regimes affect the prevalence of subminimum wage payments. We find strong evidence that higher minimum wages lead to a greater prevalence of subminimum wage payments. We consistently estimate that increases in measured underpayment following minimum wage increases average between 10 and 25 percent of realized wage gains. We interpret this as evidence that minimum wage evasion and avoidance are an important reality in the low-wage labor market. Finally, we find that enforcement regimes play an important role in shaping both baseline compliance rates and the response of compliance to increases in minimum wages.
Keywords: J08; J38; K42; 330; minimum wage; subminimum wage; compliance; noncompliance; enforcement